PERSPEKTIF PENEGAKAN HUKUM TERHADAP BARANG-BARANG ILEGAL DI PASAR BEBAS (Universitas Suryakancana, 2016)
Evil will not disappear by itself, otherwise crimes are becoming more frequent and the most dominant type of criminal offense against property, particularly those included in it is a criminal offense fencing. Criminal offenses against property will become increasingly prevalent in developing countries, the increase is in line with economic growth and development, environmental and economic factors, and not least the slide members of the public in the case of fencing Keywords : Crime against Illegal goods.